(3GdOQ GdefKhQ ef GdeCKhQ hZjQ GdeCKhQs - (3Ydj Hf eMeO Hf GdMSf Hf GdTgjO GdKGfj GdYGedj,J (B1064 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd Cbd GdYHGO Ydi Hf eMeO Hf GdMSjf Cfg deG cGf jSCdfi HYV GdENhGf ai GdOjf Yf Md CMGOjK hQOJ Yf GdCFeg GdHGOjf s
(3BNQgG (B:s
(3gPG LRGFi dge HCLQ Gdge Cdajg hbO hUdhG HGdbQH bO MUdh gPG hMRfi Ydjge dG EfbVG dg MJi CQGOge YjGfkG MjKeG fRdhG hbO Je GdLRA GdKGfi ef cJGH GdOQ GdefKhQ ai GdeCKhQ ZjQ GdeCKhQ hHg Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HChdgG agQSJ ddOQ GdefKhQs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs